2021
DOI: 10.3390/ijerph18062986
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Optimization for the Remediation of Ammonia: A Case Study Based on Electrochemical Oxidation

Abstract: This case study covers the application of the fuzzy optimization in simultaneously satisfying various constraints that include the compliance of ammonia and nitrate concentrations with stringent environmental standards. Essential components in the multi-criteria decision-making analysis is in the utilization of the Box-Behnken design (BBD) response equations, cost equations and the cumulative uncertainty of response towards the sodium chloride dosage, current density and electrolysis time parameters. The energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…As seen in Figure 5 a, the NH 3 -N concentration of sample I and sample II decreased from 853 ± 61 mg/L and 684 ± 48 mg/L to 296 ± 28 mg/L and 359 ± 22 mg/L in 120 min of EO treatment, respectively. The same conclusion should be drawn with COD and TOC results, that is, EO treatment by Ti 4 O 7 anode is more suitable for the pretreatment of wastewater containing high-concentration NH 3 -N. Previous studies have found that the indirect oxidation by HClO generated in EO system and deprotonation by hydroxyl ions on anode contributed to the removal of ammonia [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Resultssupporting
confidence: 61%
“…As seen in Figure 5 a, the NH 3 -N concentration of sample I and sample II decreased from 853 ± 61 mg/L and 684 ± 48 mg/L to 296 ± 28 mg/L and 359 ± 22 mg/L in 120 min of EO treatment, respectively. The same conclusion should be drawn with COD and TOC results, that is, EO treatment by Ti 4 O 7 anode is more suitable for the pretreatment of wastewater containing high-concentration NH 3 -N. Previous studies have found that the indirect oxidation by HClO generated in EO system and deprotonation by hydroxyl ions on anode contributed to the removal of ammonia [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Resultssupporting
confidence: 61%
“…A finer technique, photoelectrooxidation, is utilized for the more effective and time-efficient degradation of chemicals. , However, EO partially degrades the chemical components. There is a necessity for the mineralization process. , Recent studies have focused on the microbial degradation of toxic residues from organic compounds. Microbes play a pivotal role in eliminating contaminated chemical components from water environments, offering a cost-effective means of detoxifying nicotinoids . Previous research has identified various microbes with exceptional degrading abilities, including Bacillus thuringiensis, Hymenobacter latericoloratus, Ensifer meliloti, Stenotrophomonas maltophilia , and Fusarium sp . ,, Studies on biodegradation of NEOs are limited, and the researcher works on elucidating the mechanism during biodegradation. ,, Further, the detailed biodegradation process and metabolic pathway of IM can oxidatively cleave guanidine residues to produce 6-chloronicotinic acid, which is then transformed into nontoxic CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…There is a necessity for the mineralization process. 20 , 21 Recent studies have focused on the microbial degradation of toxic residues from organic compounds. 22 − 24 Microbes play a pivotal role in eliminating contaminated chemical components from water environments, offering a cost-effective means of detoxifying nicotinoids.…”
Section: Introductionmentioning
confidence: 99%